2009
DOI: 10.1111/j.1600-0560.2009.01273.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of malignancy‐associated laminins and laminin receptors by angiotropic human melanoma cells in a chick chorioallantoic membrane model

Abstract: This study shows that several genes related to laminin are overexpressed in angiotropic melanoma areas vs. avascular melanoma areas. Since extravascular migration of melanoma cells along vessels has been demonstrated in the CAM model, taken together these results suggests that some laminins and laminin receptors may play a role in extravascular migratory metastasis. This model may represent a promising strategy to analyze differential gene expression in EVMM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 30 publications
(57 reference statements)
0
29
0
Order By: Relevance
“…[48][49][50] It has been shown that melanoma cells are separated from endothelial cells by an amorphous matrix containing 'free' laminin, which is not incorporated into the basement membrane, forming an 'angio-tumoral complex'. 48,49,51 The presence of the C16 laminin peptide increases the distance of angiotropic migration of melanoma cells in vitro. 52 Furthermore, ex vivo and in vivo studies with time-lapse video microscopy have documented the migration of melanoma cells along the abluminal surface of vascular channels without blood vessel invasion, arguing against angiotropism just representing an early stage in the vascular invasion process.…”
Section: Extravascular Migratory Metastasis and Angiotropismmentioning
confidence: 99%
“…[48][49][50] It has been shown that melanoma cells are separated from endothelial cells by an amorphous matrix containing 'free' laminin, which is not incorporated into the basement membrane, forming an 'angio-tumoral complex'. 48,49,51 The presence of the C16 laminin peptide increases the distance of angiotropic migration of melanoma cells in vitro. 52 Furthermore, ex vivo and in vivo studies with time-lapse video microscopy have documented the migration of melanoma cells along the abluminal surface of vascular channels without blood vessel invasion, arguing against angiotropism just representing an early stage in the vascular invasion process.…”
Section: Extravascular Migratory Metastasis and Angiotropismmentioning
confidence: 99%
“…Laminin, a major structural component of the basement membrane, drives cell proliferation, differentiation, adhesion and migration via integrins and other cell surface receptors (1)(2)(3)(4)(5)(6)(7)(8). Increased laminin expression was also observed in melanoma cell lines and led to increased melanoma cell proliferation and metastatic potential (1-7).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of laminin and type-IV (1-7) collagen (6,7,(9)(10)(11) has also been demonstrated in melanoma cell lines with increased proliferation and metastatic potential (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of these peptides to integrins avb3 and a5b1 was rather surprising since these integrins are not classical LM receptors In cancer, a peculiar mechanism of tumour cell dissemination was described where tumour cells migrated along the external surface of vessels; this mechanism is called extravascular migratory metastasis (Lugassy and Barnhill, 2007). In the CAM assay, the C16 peptide was shown to increase extravascular migration of human GFP labelled melanoma cells along vessels although it was not addressed whether it affected angiogenesis (Lugassy et al, 2009). Because of the putative significance of this LMg1 sequence in modulating angiogenesis, had searched for a more potent peptide and discovered C16Y which was five times more active.…”
Section: Activation Of Signalling Pathways In Response To Cell Interamentioning
confidence: 99%